Vpliv postmoderne družbe na odnos medicinskih sester do komplementarnih metod zdravljenja - Kvas, Andreja (Obzornik zdravstvene nege, 2004)
The purpose of the present article was to find out the attitude of nurses towards complementary and natural healing methods in the Ljubljana region. 274nurses, participants of the symposium on complementary and natural methods in nursing care, took part in the research study. Comparative sample consistedof 105 nurses from the Hospital Centre in Ljubljana. The results of the research revealed that nurses are well acquainted with the significance ofcomplementary and natural healing methods (the control group a little less so), while there is still much confidence in conventional methods in both groups. 92 % of the symposium participants would like to get better acquaintedwith complementary methods, and half of them would like to use them in their professional work.
Keywords: Alternative Medicine; Alternativna medicina; ankete; Attitude To Health; komplementarno zdravljenje; medicinske sestre; Nursing Care; Odnos do zdravja; Questionnaires; Zdravstvena nega